Study and design of an electronic access control to “Al Raudah al Sharifah” via smart card in order to manage the crowds: دراسة وتصميم تحكم إلكتروني في الدخول إلى "الروضة الشريفة" باستخدام البطاقة الذكية من أجل إدارة الحشود - Rim Dhaou Hamdaoui, Muteeah Ahmad Aljawarneh, (Journal of engineering sciences and information technology, 2021)
This paper deals with the research of organizing and managing crowds during the visit of the Holy Raudah in the Prophet’s Mosque and. The everyday noticed fact is the visitors crowding in an attempt to enter the honourable place to pray in it.In this work, we propose the idea of designing and creating an electronic access control to enter the Holy Raudah via using a smart card. These cards are enabled to visitors with certain studied policies. They will be programmed with well-thought-out settings that contribute to organize the crowds during the entry through electronic portals. The implementation of the proposed idea is based on RFID technology and ARDUINO controller, used together to make an explanatory prototype. This solution, if applied and adopted, will offer to visitors and in particular women visitors, sufficient time to perform their rituals in the best way without harm or discomfort.